Pediatric Ventilator-Associated Infections: The Ventilator-Associated INfection Study. Issue 1 (January 2017) - Willson, Douglas F.; Hoot, Michelle; Khemani, Robinder; Carrol, Christopher; Kirby, Aileen; Schwarz, Adam; Gedeit, Rainer; Nett, Sholeen T.; Erickson, Simon; Flori, Heidi; Hays, Spencer; Hall, Mark
Abstract : Objective: Suspected ventilator-associated infection is the most common reason for antibiotics in the PICU. We sought to characterize the clinical variables associated with continuing antibiotics after initial evaluation for suspected ventilator-associated infection and to determine whether clinical variables or antibiotic treatment influenced outcomes. Design: Prospective, observational cohort study conducted in 47 PICUs in the United States, Canada, and Australia. Two hundred twenty-nine pediatric patients ventilated more than 48 hours undergoing respiratory secretion cultures were enrolled as "suspected ventilator-associated infection" in a prospective cohort study, those receiving antibiotics of less than or equal to 3 days were categorized as "evaluation only, " and greater than 3 days as "treated." Demographics, diagnoses, comorbidities, culture results, and clinical data were compared between evaluation only and treated subjects and between subjects with positive versus negative cultures. Setting: PICUs in 47 hospitals in the United States, Canada, and Australia. Subjects: All patients undergoing respiratory secretion cultures during the 6 study periods. Interventions: None. Measurements and Main Results: Treated subjects differed from evaluation-only subjects only in frequency of positive cultures (79% vs 36%; p < 0.0001). Subjects with positive cultures were more likely to have chronic lung disease, tracheostomy, and shorter PICU stay, but there were no differences in ventilator days or mortality. Outcomes were similar in subjects with positive or negative cultures irrespective of antibiotic treatment. Immunocompromise and higher Pediatric Logistic Organ Dysfunction scores were the only variables associated with mortality in the overall population, but treated subjects with endotracheal tubes had significantly lower mortality. Conclusions: Positive respiratory cultures were the primary determinant of continued antibiotic treatment in children with suspected ventilator-associated infection. Positive cultures were not associated with worse outcomes irrespective of antibiotic treatment although the lower mortality in treated subjects with endotracheal tubes is notable. The necessity of continuing antibiotics for a positive respiratory culture in suspected ventilator-associated infection requires further study. Abstract : Supplemental Digital Content is available in the text.